Evaluating fluctuations in homicide: crowdsourcing trends and assessing sentiments of change - Mancik, Ashley M. (Journal of crime and justice, 2021)
Guided by both recent anecdotal speculation of and realized statistical spikes in homicide and violence in several major U.S. cities, this study presents results of an effort to empirically examine the nature and correlates of recent changes in homicide rates (i.e. 2012–2018) with particular attention to a spike in 2014–2016 in select U.S. cities. Data were derived from multiple sources using a unique mixed-methods approach. To measure the magnitude of changes in homicide rates in recent years, quantitative homicide data were collected from the Uniform Crime Reports, media articles, individual police department queries, Project Safe Neighborhood grantee sites, and the Major Cities Chiefs Association, Violent Crime Survey. Qualitative assessments were then captured from both academic experts as well as practitioners in the field relative to the possible correlates of these observed trends. Quantitative findings substantiate that homicide rates in select U.S. cities were increasing but variation was also found with rates in other cities having remained stable or even declining over the period studied. This work delineates the practical contours of these correlates and finds concordance of practitioner beliefs with research findings while providing a glimpse toward future actions in response to both real and perceived fluctuations.